TESTING AMD RYZEN MICROPROCESSOR AND ITS ENERGY EFFICIENCY: TESTING AMD RYZEN MICROPROCESSOR AND ITS ENERGY EFFICIENCY - Denev , Daniel (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper, we show a case study of Ryzen processor energy efficiency using SPECjbb2015 as the workload. We analyze it in comparison to Phenom II, a CPU of previous generation from the same manufacturer AMD. In terms of maxi-mum transaction throughput, Ryzen performs 218% of Phenom. With the response time constraint, the relative performance of Ryzen is 288%. In the energy efficiency, Ryzen achieves 309% (at maximum throughput) and 389% (with response time constraints) of Phenom. Dynamic frequency scaling (DFS) is effective for reducing the power consumption of both processors, but the load levels at which DFS is most effective are quite different.